Neutralization and Whistleblowing: An empirical examination - Brekashvili, Paata (2012)
Neutralization theory, which explains internal excuse-making behavior, is adopted from criminology and policy compliance research and theoretically incorporated with a climate of silence model from extant whistleblowing research. Through an empirical test utilizing scenario-based field research, neutralization and climate of silence are demonstrated to jointly predict whistleblowing intentions